2015
DOI: 10.1007/s10072-015-2436-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of olive oil-based ketogenic diet on serum lipid levels in epileptic children

Abstract: Ketogenic diet (KD) is one of the most effective therapies for intractable epilepsy. Olive oil is rich in monounsaturated fatty acids and antioxidant molecules and has some beneficial effects on lipid profile, inflammation and oxidant status. The aim of this study was to evaluate the serum lipid levels of children who were receiving olive oil-based KD for intractable seizures at least 1 year. 121 patients (mean age 7.45 ± 4.21 years, 57 girls) were enrolled. At baseline and post-treatment 1, 3, 6, and 12 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 32 publications
0
21
0
1
Order By: Relevance
“…146 Strategies to prevent KDinduced hyperlipidemia include increasing consumption of MCT and olive oil, supplementing with omega-3 fatty acid or carnitine while decreasing the intake of trans fat, saturated fat, and cholesterol; decreasing the KD ratio; and excluding all fatty meats, egg yolk, cream, butter, animal fat, palm oil and coconut oil; and using a solely formulabased KD. [146][147][148] Although the risk for coronary artery disease may increase with long-term elevations of cholesterol levels, previous pediatric studies showed no change in the carotid intima-media thickness compared to baseline at 6 and 12 months of therapy. 150,151 On the other hand, local and systemic arterial stiffness was significantly increased in 2 studies involving children and young adults, correlated with serum cholesterol and triglycerides levels.…”
Section: Adverse Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…146 Strategies to prevent KDinduced hyperlipidemia include increasing consumption of MCT and olive oil, supplementing with omega-3 fatty acid or carnitine while decreasing the intake of trans fat, saturated fat, and cholesterol; decreasing the KD ratio; and excluding all fatty meats, egg yolk, cream, butter, animal fat, palm oil and coconut oil; and using a solely formulabased KD. [146][147][148] Although the risk for coronary artery disease may increase with long-term elevations of cholesterol levels, previous pediatric studies showed no change in the carotid intima-media thickness compared to baseline at 6 and 12 months of therapy. 150,151 On the other hand, local and systemic arterial stiffness was significantly increased in 2 studies involving children and young adults, correlated with serum cholesterol and triglycerides levels.…”
Section: Adverse Effectsmentioning
confidence: 99%
“…137,[145][146][147][148] Increased serum triglycerides and total and low-density lipoprotein (LDL) cholesterol levels have been reported in 14-59% of children on the classic KD. 129,137,147,148 Hyperlipidemia can be seen as early as the first month of therapy. 148 Preliminary data suggest that despite an early increase in serum lipids during the first months of KDT, this increase is usually temporary.…”
Section: Adverse Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, the combined nutritional strategy we propose herein would most likely be beneficial as, besides its much lower fat content, it provides several nutrients with beneficial effects. Indeed, polyunsaturated fatty acids provided in rapeseed oil were found to improve lipid content of children with hypercholesterolaemia 43 and a polyunsaturated fatty acids rich olive oil based KD showed reduced dyslipidaemia 44 . Medium-chain fatty acids have also been found to reduce cholesterol, triglycerides and lipoproteins levels 36 .…”
Section: Discussionmentioning
confidence: 99%
“…The best withdrawal rate of antiepileptic monotherapy in seizure-free adult patients with epilepsy is questionable [157]. Ketogenic diet (KD) is one of the most effective therapies for intractable epilepsy, and, even if rich in olive oil, high-fat KD causes significant increase in LDL-cholesterol and triglyceride levels [158].…”
Section: Epilepsymentioning
confidence: 99%